Investigating optimum ship route in the Antarctic in presence of sea ice and wind resistances – A case study between Bharati and Maitri - Mishra, Poonam; Alok, Shivang; Rajak, D. Ram; Beg, Javed M.; Bahuguna, I.M.; Talati, Isha (Polar Science, 2021)
This paper presents a technique of ship route optimization in the Antarctic sea ice region using Dijkstra's algorithm. It studies some of the major parameters that cause resistance to the ship movement through sea ice. It aims to optimize a safe ship route in the Antarctic sea ice between Bharati and Maitri (Indian Research Stations in Antarctica) coasts. The study region is divided into grids that results into unique nodes, which are studied for sea ice parameters and wind velocity. Resistances caused due to ice and wind are considered to calculate expected ship velocity between nodes. The calculated ship velocities are then used to estimate durations to cover distances from a node to all the neighboring nodes. It forms a mathematical route from source to destination through various nodes with time as weight that is then optimized through Dijkstra's algorithm to obtain optimal route. Satellite remote sensing data derived sea ice parameters (Scatsat-1 derived sea ice extent and NSIDC sea ice concentration) and modeled wind velocity (from ECMWF) have been used as inputs in this model. Ship parameters of Kapitan Khlebnikov (Russian icebreaker) are used to test and compare the proposed model. Results of model are validated with the actual ship route navigated by the 33rd Indian Scientific Expedition to Antarctica (33ISEA) ship. The proposed algorithm, which provides an optimal route when ship parameters are known in advance, can be useful to support future ship navigation in the Antarctic sea ice including Indian Scientific Expeditions to Antarctica. journal article